Proposta de uma Unidade de Ensino Potencialmente Significativa (UEPS) para Ensino de Indução Eletromagnética - Rigamonte, Fabiana (2023)
The Brazilian educational system is constantly challenged to find alternatives for the teaching-learning process, especially after the coronavirus pandemic. In parallel, the Ministry of Education implemented the new model for High School. Therefore, it is very important to prepare a proposal for adaptation and transition to the new reality and also to correct past problems. With this in mind, we propose here a Physics teaching sequence through experimentation anchored in the Learning Theory proposed by David Ausubel. From this perspective, the teacher assumes the role of mediator with the aim of placing students as protagonists of the teaching-learning process. This work presents a didactic sequence to support teachers working in New High School. The proposal was developed as a teaching-learning strategy about Electromagnetic Induction for high school students. Furthermore, we wish to associate a didactic sequence with different experiments to address the topic. The product was applied to two classes in the second year of New High School, one with a Mechanics Itinerary and the other with an Electrical Itinerary, at a private school in the city of Aracruz. The research subjects are High School students with age among 15 and 16, residing in the Aracruz city and neighboring cities. To achieve the objectives, a sequence of classes was designed where students will debate the Earth magnetic field, magnetizable materials and classes with demonstrations of magnetic phenomena with structured experimental scripts and ending with a diagnostic assessment on the topic.